1999
DOI: 10.1002/jbmr.5650140216
|View full text |Cite
|
Sign up to set email alerts
|

Paget's disease: Acquired resistance to one aminobisphosphonate with retained response to another

Abstract: Twenty-five years after the first paper on etidronate in Paget's disease, there are few published papers that address bisphosphonate resistance as a specific clinical phenomenon. We report our data from two studies. Study 1 is a retrospective study of 20 patients with moderate to severe disease who were treated with intravenous (iv) However the minimum duration of biochemical remission was significantly shorter after the second course-10.9 i 1.7 months (first) and 5.6 f 0.9 months (second) (p c 0.03; Friedman'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 17 publications
(2 reference statements)
1
24
0
Order By: Relevance
“…In Paget's disease, by contrast, where therapy is aimed at achieving complete biochemical remission, resistance to bisphosphonates has been demonstrated by several researchers. The lack of a complete biochemical remission is regarded by some as the criterion for bisphosphonate resistance [10], whereas according to others [11], the latter is established by a lower than 50-per-cent decrease in serum alkaline phosphatase (AP) level. Notwithstanding the criteria, the prevalence of resistance varies with different bisphosphonates in the range between 83% (etidronate [10]) and 11% (zolendronate [12]).…”
Section: Introductionmentioning
confidence: 99%
“…In Paget's disease, by contrast, where therapy is aimed at achieving complete biochemical remission, resistance to bisphosphonates has been demonstrated by several researchers. The lack of a complete biochemical remission is regarded by some as the criterion for bisphosphonate resistance [10], whereas according to others [11], the latter is established by a lower than 50-per-cent decrease in serum alkaline phosphatase (AP) level. Notwithstanding the criteria, the prevalence of resistance varies with different bisphosphonates in the range between 83% (etidronate [10]) and 11% (zolendronate [12]).…”
Section: Introductionmentioning
confidence: 99%
“…As a counterpart, acquired resistance to the intravenous infusion of some amino-bisphosphonates such as pamidronate has been reported in different studies. (9,15,18,19) In one of these studies, we demonstrated that intravenous infusions with either zoledronate or neridronate are effective in achieving therapeutic response at 6 months in up to 90% of patient nonresponders to multiple courses of pamidronate. (15) Results from this study confirm and extend these observations and indicate that a single course with neridronate 200 mg is effective and normalizes bone turnover in up to 85% of patients with PDB within the first year of treatment and in up to 55% after the second year.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects were evaluated at baseline and after 3,6,12,18,24,30 The primary efficacy endpoint was the rate of therapeutic response assessed at 6, 12, 24, and 36 months and defined as the normalization of ALP levels or a reduction of at least 75% in total ALP excess (the difference from the midpoint of the reference range). Secondary endpoints were the reduction of bone pain, time of nadir of ALP (defined as the number of days from the beginning of the treatment to the time when the lowest value was observed), time to a therapeutic response (defined as the number of days between the onset of treatment and the visit at which a response was observed), and the average percent decrease in ALP or the other bone turnover markers at each time point compared with baseline levels.…”
Section: Biochemical Evaluation and Efficacy Endpointsmentioning
confidence: 99%
“…Use of acetaminophen or a nonsteroidal anti-inflammatory drug (NSAID) is very helpful in ameliorating the self-limited flu-like symptoms. Finally, physicians should be aware that acquired or secondary resistance to both etidronate and pamidronate (16,23,24) have been described, with less robust decreases in bone turnover markers or reductions in the duration of biochemical remissions or both with repeated courses of therapy. It seems that switching to a different bisphosphonate is effective in restoring a better treatment response.…”
Section: Clinical Comments Recommendations and Caveatsmentioning
confidence: 99%
“…It seems that switching to a different bisphosphonate is effective in restoring a better treatment response. (24) It is unclear at this time whether acquired resistance occurs with the other approved agents.…”
Section: Clinical Comments Recommendations and Caveatsmentioning
confidence: 99%